Factors contributing to fatal snake bite in the rural tropics: analysis of 46 cases in Thailand. - Looareesuwan, S; Viravan, C; Warrell, D (1988)
Records of 46 cases of fatal bites by identified snakes from 15 provincial hospitals throughout Thailand contained sufficient information for detailed analysis. Bungarus candidus and Calloselasma rhodostoma were each responsible for 13 deaths, Naja kaouthia for 12, Vipera russelli for 7 and B. fasciatus for one. Major causes of death among elapid victims were respiratory failure (26) and complications of prolonged mechanical ventilation (10), and among viper victims shock (12), intracranial haemorrhage (9), complications of local wound necrosis (7) including tetanus (2), and renal failure (2). Factors contributing to fatal outcome included inadequate dose of antivenom (15 cases), misidentification of the snake leading to use of the wrong antivenom (12), problems associated with mechanical ventilation (10), and delayed arrival in hospital after traditional (herbal) treatment (10). Similar problems have been identified in other tropical countries. Education of medical staff and the patient population at highest risk could reduce snake bite mortality.